O impacto do planejamento estratégico na elaboração e implementação do plano de gerenciamento de resíduos de serviços de saúde na atenção básica - Alves, Sergiane Bisinoto (2015)
The waste management is still deficient in many healthcare services. Those healthcare services smaller, as the primary healthcare offices, this problem becomes greater. Also important the destination for healthcare waste management generated by professionals and users in households. Faced with the expansion of the number and specificities of units in primary healthcare of occupational, environmental and social risks represent by healthcare waste generated in these environments, if not correctly managed, interventions in these realities are necessary and urgent. The objective was to evaluate the impact of the implementation of a healthcare waste management plan in primary healthcare unit and to check the approaches adopted by healthcare workers on the management of piercing and cutting waste generated by insulin users at households. This is a comparative and intervention study, pre and post, in a non-hospital unit to emergency care and also in a family healthcare unit, in the period from 2011 to 2014. The intervention performed consisted of: design and implementation of healthcare waste management plan using the situational strategic planning, educational and illustrative activities for users and multimodal permanent education, collective and individualized, for professionals for both healthcare units. A year after the intervention, all waste generated during a week in each healthcare unit were weighed and analyzed about the segregation. The values obtained were compared to those in the pre-intervention phase (Alves, 2010) that made the diagnosis in the same units and used the same methodology for the quantification and segregation analysis of the healthcare waste. The results show that the development and implementation of the waste management plan, using the situational strategic planning reduced healthcare waste generation and the inadequacies found about segregation in both units studied. It was also observed that there isn´t a management plan about management of piercing and cutting waste generated by users in households and that management is not assimilated in professional practice or in institutional procedures. The proposed intervention proved to be easy to apply and to involve all professionals and managers in prepare and implementation of a healthcare waste management plan in primary healthcare unit. The professionals and managers actively participated since the diagnosis of the healthcare waste management situation, discussion of alternatives to solve the problems listed until the decision making, resulting in a collective commitment to implement the healthcare waste management plan of healthcare services.